Frozen or malleable? Political ideology in the face of job loss and unemployment. (20th May 2019) - Wiertz, Dingeman; Rodon, Toni
Abstract: To what degree do people adjust their political ideology in response to job loss? To answer this question, we draw on Dutch panel data over the period 2007–2016, paying special attention to the potential moderating role of various personal circumstances. We find that, on average, job loss triggers a leftward ideological response. Although small in size, this shock effect persists when people remain unemployed or find new employment, yet in the longer run it wears off. Furthermore, we find that job loss prompts a bigger shift to the left when people are simultaneously confronted with a major drop in household income, when they have fewer financial resources to serve as a buffer, and when they are more pessimistic about the economy. While we also observe many people who revise their ideology to the right during our study window, these rightward shifts do not seem driven by job loss experiences.